Calcium, diet and fracture risk: a prospective study of 1898 incident fractures among 34 696 British women and men. - Key, T; Appleby, P; Spencer, E; Roddam, A; Neale, R; Allen, N (2007)
OBJECTIVE: The risk factors for fractures are incompletely understood. An outstanding question concerns the optimal amount of dietary calcium needed to minimise the risk of fracture. DESIGN: We examined the associations of dietary calcium and other nutrients with self-reported fracture risk in a prospective cohort study. Nutrient intakes were estimated using a semi-quantitative food-frequency questionnaire administered at recruitment. SETTING: The UK. PARTICIPANTS: A total of 26 749 women and 7947 men aged 20-89 years. RESULTS: Over an average of 5.2 years of follow-up, 1555 women and 343 men reported one or more fractures, 72% of these resulting from a fall. Among women, fracture risk was higher at lower calcium intakes, with a relative risk of 1.75 (95% confidence interval (CI) 1.33-2.29) among women with a calcium intake of < 525 mg day- 1 compared with women with a calcium intake of at least 1200 mg day- 1 (test for linear trend, P < 0.001). The association of dietary calcium with fracture risk was stronger among women aged under 50 years at recruitment than among women aged 50 and above. Dietary calcium intake was not associated with fracture risk in men. Fracture risk was not related to the dietary intake of any other nutrient examined. CONCLUSION: In this population, women with a low dietary calcium intake had an increased risk of bone fracture, and this association was more marked among younger women than among older women.